Graphene integrated polyaniline nanostructured composite coating for protecting steels from corrosion: Synthesis, characterization, and protection mechanism of the coating material in acidic environment. (15th July 2016) - Mahato, Neelima; Cho, Moo Hwan
Abstract : Graphical abstract: Highlights: The synthesized materials show good crystalline properties. The coating show good protection to MS against uniform corrosion. Graphene loading of 1.92 wt.% exhibit best protection. Graphene integration prevents conformational change of the Pani. The composite coatings are hydrophobic to repel moisture. Abstract: We report on the synthesis, characterization and application of highly crystalline graphene integrated polyaniline nanostructured composites as corrosion protection coatings. The coated surface showed a decline in corrosion current up to ∼3–4 orders of magnitude in 0.1 M HCl. Composite coating with 1.92 wt.% graphene loading showed best protection. SEM images obtained after the corrosion tests reveal several pits on the coated steel surface with network like structures. A plausible mechanism of the corrosion protection mechanism of the composite coating has been proposed to explain the fate of the material in acidic environment.